1H‐NMR metabolomics for evaluating the protective effect of Clinacanthus nutans (Burm. f) Lindau water extract against nitric oxide production in LPS‐IFN‐γ activated RAW 264.7 macrophages. Issue 1 (5th September 2018) - Khoo, Leng Wei; Kow, Audrey Siew Foong; Maulidiani, Maulidiani; Ang, May Yen; Chew, Won Yin; Lee, Ming Tatt; Tan, Chin Ping; Shaari, Khozirah; Tham, Chau Ling; Abas, Faridah
Abstract: Introduction: Clinacanthus nutans, a small shrub that is native to Southeast Asia, is commonly used in traditional herbal medicine and as a food source. Its anti‐inflammation properties is influenced by the metabolites composition, which can be determined by different binary extraction solvent ratio and extraction methods used during plant post‐harvesting stage. Objective: Evaluate the relationship between the chemical composition of C. nutans and its anti‐inflammatory properties using nuclear magnetic resonance (NMR) metabolomics approach. Methodology: The anti‐inflammatory effect of C. nutans air‐dried leaves extracted using five different binary extraction solvent ratio and two extraction methods was determined based on their nitric oxide (NO) inhibition effect in lipopolysaccharide‐interferon‐gamma (LPS‐IFN‐ γ ) activated RAW 264.7 macrophages. The relationship between extract bioactivity and metabolite profiles and quantifications were established using 1 H‐NMR metabolomics and liquid chromatography–tandem mass spectrometry (LC–MS/MS). The possible metabolite biosynthesis pathway was constructed to further strengthen the findings. Results: Water and sonication prepared air‐dried leaves possessed the highest NO inhibition activity (IC50 = 190.43 ± 12.26 μg/mL, P < 0.05). A total of 56 metabolites were tentatively identified using 1 H‐NMR metabolomics. A partial least square (PLS) biplot suggested that sulphur containing glucoside, sulphur containing compounds, phytosterols, triterpenoids, flavones and some organic and amino acids were among the potential NO inhibitors. LC–MS/MS targeted quantification further supported sonicated water extract was among the extract that possessed the most abundant C‐glycosyl flavones. Conclusion: The present study may serve as a preliminary reference for the selection of optimum extract in further C. nutans in vivo anti‐inflammatory study. Abstract : Clinacanthus nutans (Burm. f) Lindau is a vegetable and herb that native to Southeast Asia. Present study aims to evaluate the relationship between the chemical composition and the anti‐inflammatory properties of C. nutans using NMR metabolomics approach. Water‐sonication prepared air‐dried leaves exhibited the highest NO inhibition activity in LPS‐IFN‐ γ activated RAW 264.7 macrophages (IC50 : 190.43 ± 12.26 μg/mL). Sulfur containing glucoside, sulfur containing compounds, phytosterols, triterpenoids, flavones and some organic and amino acids were among the potential NO inhibitors.